2001
DOI: 10.1016/s0273-1177(01)00172-7
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric effects of the solar flares as deduced from global GPS network data

Abstract: Results derived from analysing the ionosphere response to faint and bright solar flares are presented. The analysis used technology of a global detection of ionospheric effects from solar flares as developed by the authors, on the basis of phase measurements of the total electron content (TEC) in the ionosphere using an international GPS network. The essence of the method is that use is made of appropriate filtering and a coherent processing of variations in the TEC which is determined from GPS data, simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…By virtue of the fact that the response amplitude at high altitudes was found to be comparable with the level of background fluctuations, the method of coherent accumulation by Afraimovich (2000a) and Afraimovich et al (2000bAfraimovich et al ( , 2001a was used in an additional analysis. The essence of the method is that it involves a coherent summation of TEC responses to the solar flare, which are measured simultaneously with all LOS chosen for the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By virtue of the fact that the response amplitude at high altitudes was found to be comparable with the level of background fluctuations, the method of coherent accumulation by Afraimovich (2000a) and Afraimovich et al (2000bAfraimovich et al ( , 2001a was used in an additional analysis. The essence of the method is that it involves a coherent summation of TEC responses to the solar flare, which are measured simultaneously with all LOS chosen for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For flares lying closer to the disk center (CMD < 40 • ), an empirical dependence of the ionospheric TEC increase amplitude on the peak power of solar flares in the X-ray range was obtained (using data from the geostationary GOES-10 satellite). This paper is a logical continuation of the series of our publications (Afraimovich, 2000a;Afraimovich et al, 2000bAfraimovich et al, , 2001aAfraimovich et al, , b, c, 2002Leonovich et al, 2001) devoted to the study of ionospheric effects of solar flares, based on data from the international GPS network.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Since the beginning of 21st century, the twodimensional imaging technique using TEC data from worldwide GPS receiver networks has been applied to SITEC studies [e.g., Afraimovich et al, 2001;Liu and Lin, 2004]. These studies have observed a solar zenith angle (SZA) dependence of SITEC [Zhang and Xiao, 2003;Wan et al, 2005].…”
Section: Introductionmentioning
confidence: 99%